Mechanical Postbuckling Behavior of Circular Plates Through Concept of Equivalent Radial Tensile Load - G., Venkateswara Rao; Ramaraju, Ramgopal Varma (2013)
Aerospace and automobile structural systems are assemblages of simple structural members like, columns, circular and rectangular plates etc., designed with lesser margins of safety and also have minimum mass, are subjected to severe mechanical or thermal loads during the service conditions. As such, these structural members are relatively more flexible, compared to the same used in the other fields of engineering. Due to these requirements, the study of the thermal or mechanical postbuckling behavior of these structural members gained importance. To predict the mechanical or thermal postbuckling behavior of these structural members, a more rigorous geometric nonlinear (large deflections) analysis is required. The present study deals with the concept of the effective tensile load developed, due to large deflections, to derive a simple heuristic formula, called simply as the formula, to predict the mechanical postbuckling behavior of circular plates, called simply as plates, without going for complex mathematical treatment1,2. The circular plate problem,formulated in the polar coordinate system, is relatively more involved, as the radial and circumferential strains are coupled by the radial displacement, compared to the other structural members, which are formulated in the Cartesian coordinate system. Such formulas are handy and useful to the designers/analysts to quickly evaluate the mechanical postbuckling behavior of the plates, in the iterative design/analysis cycles